1993
DOI: 10.1007/bf02072513
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte production of gamma-interferon as a test for non-tuberculous mycobacterial lymphadenitis in childhood

Abstract: Infection with Mycobacterium avium, M. intracellulare and M. scrofulaceum (MAIS) organisms in normal children may result in cervical lymphadenopathy. There is a poor response to anti-tuberculous therapy and surgical excision of infected nodes is necessary. The diagnosis therefore requires consideration in children with cervical lymphadenopathy. A simple in vitro assay is described which may be useful for diagnosis prior to excision. Whole blood is cultured with M. avium purified protein derivative. After 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“… 4 (4) Furthermore, a NTM‐dominant reaction would establish the diagnosis of the adenitis in only 48 to 72 hours and allow the clinician to comfort the parents as to the benign nature of the lesion. Von Reyn et al 5 have demonstrated, using the same M. avium sensitin as in our institution, that dual skin testing distinguishes between infection resulting from MAC and infection caused by M. tuberculosis : a dominant skin test reaction was 100% specific for infection with the homologous organism. If we only consider the patients with a definitive diagnosis of NTM adenitis, the sensitivity of NTM skin testing alone is 87%.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“… 4 (4) Furthermore, a NTM‐dominant reaction would establish the diagnosis of the adenitis in only 48 to 72 hours and allow the clinician to comfort the parents as to the benign nature of the lesion. Von Reyn et al 5 have demonstrated, using the same M. avium sensitin as in our institution, that dual skin testing distinguishes between infection resulting from MAC and infection caused by M. tuberculosis : a dominant skin test reaction was 100% specific for infection with the homologous organism. If we only consider the patients with a definitive diagnosis of NTM adenitis, the sensitivity of NTM skin testing alone is 87%.…”
Section: Discussionmentioning
confidence: 80%
“…This might be explained by the 100% specificity demonstrated by von Reyn et al in their study. 5 The role of medical treatment is not well established, 14 and there has been no controlled study to support its usefulness. 15 Medications such as clarithromycin may prove effective, 14 but treatment with antituberculous drugs is usually ineffective because most NTM are resistant to the majority of antituberculous agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, any condition that alters the immune system, especially that will depress this system, theoretically can cause false-negative results with this test. [12][13][14][15][16] In the US Centers for Disease Control and Protection (CDC) guidelines of 2003, pregnancy was one of the conditions in which use of this test was not recommended, because pregnancy has the potential to decrease the immune response. 7 In the CDC guidelines of 2005, the spectrum to use QuantiFERON ® -TB Gold was broadened and pregnancy no longer showed as one of the conditions for which it is not recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Leukocytes from multiple healthy controls showed negligible IFN-␥ responses to both PPD preparations. A comparable ex vivo whole blood assay has been used for diagnosis of paratuberculosis in cattle (58,79), cervical lymphadenitis caused by M. avium in children (17,36), and leprosy (76,77).…”
mentioning
confidence: 99%